High‐performance liquid chromatographic cartridge with gradient elution capability coupled with UV absorbance detector and mass spectrometer for peptide and protein analysis. Issue 13 (9th June 2017) - Lynch, Kyle B.; Chen, Apeng; Yang, Yu; Lu, Joann J.; Liu, Shaorong
Abstract : We discuss the construction and performance of a high‐performance liquid chromatography cartridge that we developed that resulted from a culmination of previous research. We have recently developed an innovative approach to creating gradient elutions using dual electroosmotic pumps and a series of three valves. This method has been proved to be the most reproducible and robust in producing gradients compared to our previously tested methods. Using this approach, we have assembled a high‐performance liquid chromatography cartridge powered and controlled via a computer. We have successfully coupled the cartridge with an ultraviolet absorbance detector and a mass spectrometer for separating complex protein/peptide samples. The cartridge is readily coupled with other detectors such as electrochemical detector and laser‐induced fluorescence detector.